IMPACT OF WORKING ENVIRONMENT AND MOTIVATION ON DEPOK ASSALAM VOCATIONAL HIGH SCHOOL TEACHER PERFORMANCE - Luhkita, Erin Tami; Parwoto, Parwoto (Penerbit Atma Jaya Catholic University of Indonesia, 2020)
This study aims to analyze the influence of the work environment and work motivation of Depok Assalam Vocational teachers. The amount of Depok Assalam Vocational teachers involved in this study were 35 people. Assalam The technique used to determine the sample is to use saturated samples, a  method of collecting data using survey methods with questionnaire as the research instrument .The Data analysis methods used for this study is Statistical Product and Service Solutions. This study proves that environmental circumstances influenced the teachers?performance in a positive and significant way. In summary, work motivation gave a positive and  significant influence to the teachers? performance